The Use of the Fecal Immunochemical Test in the Acute-Care Hospital Setting - Román-Colón, Diego; Rodriguez-Ramos, Roberto; Cerra-Franco, Javier; De Jesús-De La Cruz, Henry; Mirza, Zeyn T.; Cepero-Jimenez, Carla; Ramos-Marquez, Reyshley; Martinez-Souss, Jaime; Toro, Doris H. (Puerto Rico Health Sciences Journal, 2025)
Objective: The fecal immunochemical test (FIT) is indicated for colon cancer screening in asymptomatic average-risk patients. However, the inclusion of orders for non-indication-based FITs in medical records has led to increased inappropriate use in emergency department (ED) and inpatient settings. This study aimed to evaluate the clinical impact of FIT results when the test is used for purposes other than routine screening. Methods: We conducted a single-center, retrospective chart review using electronic medical records, analyzing patients who underwent the FIT in the ED or while admitted to the VA Hospital from September 2013 through December 2016. The collected data included demographics; clinical symptoms and signs; medications; and information on digital rectal examinations, gastroenterology consultations, and endoscopic procedures. Results: Of the 1,354 patients included, most were men. Among FIT-positive patients, the mean age was 73.7 years. The majority of FITs were done in the ED. Positive FIT results were statistically significantly associated with rectal bleeding, weakness, and diarrhea. Anticoagulants were associated with positive FIT results. Patients with positive tests often received gastroenterology consultations and were more likely to undergo endoscopic procedures. Conclusion: None of the evaluated FITs were used for screening, confirming that they had been ordered inappropriately. This indiscriminate use can lead to unnecessary interventions and prolonged hospitalizations. Additionally, negative tests may lead to underestimate worrisome symptoms or features that require further investigation. In conclusion, our study does not support the indiscriminate use of the FIT in inpatient or ED settings.